Ask me no questions - Noble, Shelley (Noble, Shelley. Lady Dunbridge mystery., 2018)
A modern woman in 1907, Lady Dunbridge is not about to let a little thing like the death of her husband ruin her social life. She<U+2019>s ready to take the dazzling world of Gilded Age Manhattan by storm. From the decadence of high society balls to the underbelly of Belmont horse racing, romance, murder, and scandals abound. Someone simply must do something. And Lady Dunbridge is happy to oblige.